Octominin: A Novel Synthetic Anticandidal Peptide Derived from Defense Protein of Octopus minor - Nikapitiya, Chamilani (Mar Drugs, 2020)
The rapid emergence of multidrug-resistant pathogens makes an urgent need for discovering novel antimicrobial agents as alternatives to conventional antibiotics. Towards this end, we designed and synthesized a synthetic peptide of 23 amino acids (AAs) ((1)GWLIRGAIHAGKAIHGLIHRRRH(23)) from a defense protein 3 cDNA sequence of Octopus minor. The sequence of the peptide, which was named Octominin, had characteristic features of known antimicrobial peptides (AMPs) such as a positive charge (+5), high hydrophobic residue ratio (43%), and 1.86 kcal/mol of Boman index. Octominin was predicted to have an alpha-helix secondary structure. The synthesized Octominin was 2625.2 Da with 92.5% purity. The peptide showed a minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of 50 and 200 μg/mL, respectively, against Candida albicans. Field emission scanning electron microscopy observation confirmed that Octominin caused ultrastructural cell wall deformities in C. albicans. In addition, propidium iodide penetrated the Octominin-treated C. albicans cells, further demonstrating loss of cell membrane integrity that caused cell death at both MIC and MFC. Octominin treatment increased the production of intracellular reactive oxygen species and decreased cell viability in a concentration dependent manner. Cytotoxicity assays revealed no significant influence of Octominin on the viability of human embryonic kidney 293T cell line, with over 95% live cells in the Octominin-treated group observed up to 100 µg/mL. Moreover, we confirmed the antifungal action of Octominin in vivo using a zebrafish experimental infection model. Overall, our results demonstrate the Octominin is a lead compound for further studies, which exerts its effects by inducing cell wall damage, causing loss of cell membrane integrity, and elevating oxidative stress.